Trigonocephaly: results after surgical correction of nonsyndromatic isolated metopic suture synostosis in 54 cases - Engel, Michael; Thiele, Oliver C.; Mühling, Joachim; Hoffmann, Jürgen; Freier, Kolja; Castrillón-Oberndorfer, Gregor; Seeberger, Robin (Journal of cranio-maxillofacial surgery, 2011)
Children with nonsyndromatic isolated metopic suture synostosis suffer from a significant deformity of the supraorbital ridges, the temporal regions and hypotelorism. We retrospectively analyzed 54 consecutive cases of isolated nonsyndromatic metopic synostosis treated over a 14-year-period. The data were evaluated using patients’ clinical records, skull radiographs in two planes, CT-scans, MRI scans and pre-/post-operative photographs. Surgery with standardized fronto-orbital advancement was performed at a median age of 11.5 months. Follow-up ranged from 4.5 months to 177.4 months, with an average of 51.9 months. The average blood loss was less than 255ml and the average post-operative length of stay was 5 days. Not a single major complication was observed except for uncomplicated dural tears in six cases. According to the classification of Whitaker, results were considered good to excellent (Category I and II) in all except one case (Category IV). As the current techniques have been standardized for routine use, surgical risks are reasonably low with no mortality or permanent morbidity. We think that the treatment of single metopic synostosis is safe with very low reoperation rates and short length of hospital stay. Overall, our results showed acceptable minor complication rates and generally satisfactory aesthetic outcomes.
Available online 2 July 2011
Gesehen am 09.05.2018